Mild Steel Corrosion Inhibition in a NaCl Solution by Lignin Extract of Chromolaena odorata - Muzakir,M.M. (2019)
The inhibitive action of Chromolaena odorata stems extract, in various concentrations, against mild steel corrosion in a 1 M NaCl solution, was studied using weight loss, potentiodynamic polarization methods and scanning electron microscopy. Maximum inhibition efficiency of 99.83 % was obtained, at 303 K, for an extract concentration of 3000 mgL-1. The activation and free energies for the inhibition reactions supported the physical adsorption mechanism. The extract adsorption onto the mild steel surface was found to be exothermic, spontaneous, and to obey the Langmuir adsorption model. FT-IR analysis showed the presence of hydroxyl (OH) and carbonyl(C=O) functional groups and aromatic rings in lignin, which are the binding groups that might be responsible for lignin's inhibitive action against mild steel corrosion. Furthermore, SEM analysis revealed that the mild steel surface was affected by lignin's adsorption, due to the formation of a protective film.